PENTINGNYA INTERNET SEHAT - Fajar Hidayanto (UII, 2015)
Internet is a global computer network system that is connected using internetprotocol (TCP/IP) to connect devices in computers around the world. Lots ofinformation spread around the internet. Each of the access it can get any information.Under these conditions, it is very dangerous if used with any internet, especially forchildren. Similarly, author fears to children in the Desa Gerbosari, Kulonprogo, DaerahIstimewa Yogyakarta. Therefore, the authors initiated a healthy socialization of theinternet which was held in a community service activity.